Urban-Rural Differences in the Economic Burden of Type 2 Diabetes Mellitus: A Community-Based Cross-Sectional Study from Puducherry, India - Pavithran Murugan; Kavita Vasudevan; Lopamudra Debasish; Lalithambigai Chellamuthu; Poovitha Ramamurthy (National Journal of Community Medicine, 2026)
Introduction: Diabetes mellitus represents a significant public health issue and is one of the leading noncommunicable diseases in our country. Diabetes imposes a substantial financial burden due to its chronic nature and complications. The objective was to assess the annual expenditure incurred for diabetes care among the individuals with diabetes and to compare the expenditure pattern among diabetes individuals residing in urban and rural area populations in Puducherry. Methodology: A community-based analytical cross-sectional study was conducted in the field practice areas affiliated with a medical college. A total 566 participants (283 urban and 283 rural) were selected using multistage random sampling. Data were collected using a pretested semi-structured questionnaire. Statistical analysis was performed by entering the data into Microsoft Excel and subsequently analysing it using SPSS version 22. Results: The median overall total annual cost incurred by the respondents for management of diabetes was found to be Rs. 11225 (IQR 3625-22820). Direct cost accounted for >90% of total expenditure, with medications contributing the most (median ₹10,410). Rural participants incurred higher medication and hospitalisation costs, whereas urban participants had higher investigation and indirect costs. Higher family income, longer diabetes duration, and comorbidities were significantly associated with higher direct healthcare costs. Conclusions: The median overall total annual cost incurred by the respondents for management of diabetes was found to be Rs. 11225 (IQR 3625-22820). Direct cost accounted for >90% of total expenditure. Catastrophic health expenditure was higher among rural participants (39.2%) than urban participants (27.5%; p = 0.002).